IMPLEMENTATION OF DISCRIMINANT ANALYSIS IN DETERMINING OFFLINE AND ONLINE CONSUMER SHOPPING BEHAVIOR IN RETAIL MARKET - Nurlinda, R.A.; Elistia,; Simanjuntak , Darwin; Roespinoedji, Roeshartono (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to know the factors of retail mix and brand image in forming consumer preference and to know trend of offline and online shopping behavior. The data used in this study is the primary data by questionnaire. This questionnaire consists of six variables of retail mix: service quality, product diversity, price, promotion, store atmosphere, and brand image with the total number of statements that are thirty-two statements and have been tested for validity and reliability. Samples taken as many as 300 respondents. The analytical method used is discriminant analysis. Based on the calculation of the whole analysis it can be concluded that product diversity and store atmosphere are variables affecting consumer behavior in offline and online shopping on retail business and shopping behavior trends in retail business leads to offline shopping system.